Joint consensus statement and guideline on transcatheter aortic valve implantation (TAVI) in South Africa - October 2016 - Weich, Hellmuth; Scherman, Jacques (SA Heart Journal, 2017)
The South African Heart Association (SA Heart), together with 2 of its special interest groups, South African Society of Cardiovascular Intervention (SASCI) and Society of Cardiothoracic Surgeons of South Africa (SCTSSA) represent the scientific, educational, socio-economic, ethical and professional interests of South African cardiac specialists, with a combined membership of over 200 members.